The little book of baby massage : use the power of touch to calm your baby - Kellett, Jo (New York, NY : DK Publishing, 2020)
To a baby, touch is talk, and through these relaxing techniques you and your child can share some of your most fulfilling and communicative moments. Calm your little one, soothe them to sleep, and most importantly, strengthen your love, all with the wonderful power of touch. With guidance on how to incorporate massage into your baby's day-to-day routine, and techniques to ease common ailments, such as colic, teething and constipation, this book will give you everything you need to comfort your baby from head to toe. Charming illustrations and easy-to-follow instructions take you through a full-body baby massage, teaching you in detail how, when, and why to massage each part of your baby. The book also covers massaging babies of all ages, from newborns to toddlers, as well as special situations such as premature babies and adoption, helping you personalize the practice and find what's best for you and your baby to make the most of every touch. Massage is the most intimate way to soothe, nurture and relax your baby. Reinforce your loving bond with easy-to-learn massage techniques that promote all-round wellbeing - for your baby and for you.
Getting started -- Head-to-toe massage -- Your daily routine -- Easing common ailments -- Beyond baby -- Special situations.
Includes index.
Keywords: Massage for infants; Infants -- Care; HEALTH & FITNESS / Children's Health; HEALTH & FITNESS / Massage & Reflexology; MEDICAL / Alternative & Complementary Medicine; Infants -- Care; Massage for infants; Massage; Infants -- Care